The Implicit Contribution of Principal’s Self-Awareness Towards Teacher Self-Efficacy - Khun-Inkeeree, Hareesol; Abdul Aziz, Nor Azah; Mohd Yaakob, Mohd Faiz; Rahimi Yusof, Mat; Omar-Fauzee, M.S. (International Journal of Criminology and Sociology, 2022)
The main focus of this study was to look at the influence of the authentic leadership of the principals and the self-efficacy level of teachers in Pendang district, Kedah. The quantitative survey method using the questionnaire was adopted in this study. The study respondents consisted of 254 teachers randomly selected from 10 national secondary schools in Penang district, Kedah. The benchmark used for authentic leadership is to use the Authentic Leadership Questionnaire (ALQ -Version 1) of the original instrument developed by Avolio, Gardner, and Walumbwa (2007). Similarly, the teacher self-efficacy questionnaire was used in Hoy and Woolfolk’s (1993) short form of the Teacher Efficacy Scale developed by Moran, Hoy, and Hoy (1998). The findings show that there is a significant relationship between the dimensions of authentic leadership and the self-efficacy of teachers in Pendang, Kedah. However, there is only one dimension that influences the teacher’s self-efficacy, which is the dimension of self-awareness. Based on the findings of this study, it is hoped that it will contribute useful information to help educators in cultivating the principals’ leadership style and high levels of teacher self-efficacy to produce symmetrical human capital.